Detection of C. trachomatis in the Serum of the Patients with Urogenital Chlamydiosis - Petyaev, Ivan M.; Bashmakov, Yuriy K.; Kost, Elena A.; Didenko, Lubov V.; Kapotina, Lidia N.; Morgunova, Elena Y.; Rumyantseva, Yulia P.; Zigangirova, Naylia A.; Koroleva, Ekaterina A. (BioMed research international, 2013)
Extragenital chlamydial complications may be associated with systemic spread of infection, but haematogenous route for C. trachomatis dissemination has not been clearly demonstrated. Here we report that serum specimens obtained from patients with chlamydiosis contain elementary bodies of C. trachomatis shown by culture and immunogold electron microscopy. We have found that 31 of the 52 patients had serum precipitates which were infective to McCoy cells. Immunostaining revealed very small inclusions resembling those reported during persistent C. trachomatis infection in vitro. DNA specimens from 49 (out of 52) patients with chlamydiosis gave positive PCR readings. The viability of the pathogen present in the sera was confirmed by chlamydial RNA detection in the cell monolayer inoculated by the serum precipitates. By using DNA isolation protocol from 1 mL of serum and quantitative TaqMan PCR, it was estimated that bacterial load in patients’ sera was 2×102–103 GE/mL. These findings for the first time demonstrated that C. trachomatis can be disseminated directly by the plasma, independently from blood cell, which may represent a new possible pathway of the chronic infection development. Therefore, new methodological approaches for detection of C. trachomatis in the serum of patients with complicated and chronic chlamydiosis could be important in the diagnosis of the infection regardless of its anatomical localization.